Raman and SERS spectroscopy for characterization of extracellular vesicles from control and prostate carcinoma patients - Krafft, Christoph; Osei, Eric Boateng; Popp, Jürgen; Nazarenko, Irina (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2020)
Extracellular vesicles (EVs) in body fluids are promising biomarkers for cancer and other diseases. Due to their small size in the range between 50 and 800 nm, spectroscopic characterization is challenging. First Raman studies of single EVs suffered from weak signal intensities which complicated detection of small variations between different EVs. New Raman results will be presented on EVs from the blood of prostate carcinoma patients and control patients. Three EV fractions were prepared by sequential gradient centrifugation at 5000 g, 12000 g, and 120000 g called EV5, EV12, and EV120, respectively. Additionally, an EV-depleted fraction was obtained from the EV120 supernatant after additional overnight centrifugation. Nanoparticle tracking analysis and electron microscopy were used to determine particle concentration and control quality. High quality Raman spectra were collected from dried pellets using a Raman microscope at 785 nm excitation. Main spectral contributions were assigned to proteins. Protein secondary structure changes distinguished EV fractions from non-cancer and cancer patients consistent with results reported in an earlier paper. Suspensions with aggregated silver nanoparticles increased the band intensities due to the surface enhanced Raman scattering (SERS) effect at 785 nm excitation. Non-cancer EV fractions showed typical SERS bands of proteins. SERS spectra of cancer EV fractions showed an intense signature of new bands at 713, 853, 1004, 1132, 1238 and 1392 cm-1. No SERS enhancement was observed in the EV-depleted fraction. We concluded that fractions EV12 and EV120 containing small EVs are most applicable for Raman and SERS measurements.
CRIS-Team Scopus Importer:2023-04-20
Keywords: exosomes; extracellular vesicles; Raman spectroscopy; surface enhanced Raman spectroscopy